2017
DOI: 10.1590/s1679-45082017md3793
|View full text |Cite
|
Sign up to set email alerts
|

PET/MRI: a novel hybrid imaging technique. Major clinical indications and preliminary experience in Brazil

Abstract: In recent years, medical imaging with hybrid techniques has widely accepted and employed in clinical routine. PET/MRI offers significant advantages, including excellent contrast and resolution and reduced ionizing radiation, as compared to well-established PET/CT. Therefore, PET/MRI is a promising modality for oncologic imaging of some regions, such as brain, head and neck, liver and pelvis. This article set out to analyze clinical conditions that could benefit from PET/MRI imaging based on our caseload. The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 8 publications
0
10
0
3
Order By: Relevance
“…32 Furthermore, this isotopic mixture offers the possibility of combining PET ( 52 Mn) and MR ( 55 Mn) imaging modalities to provide anatomical and functional information. 33,34 In cancer diagnosis, mapping of tissue pH can potentially be used to recognize malignant processes at an early stage since the accelerated glucose metabolism of cancer cells results in a decrease of the extracellular and increase of the intracellular pH (Warburg effect). 35,36 Several Gd(III)-based pH-sensitive SCA candidates were reported relying on the pH-dependent coordination of an ethylamine pendant arm.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 Furthermore, this isotopic mixture offers the possibility of combining PET ( 52 Mn) and MR ( 55 Mn) imaging modalities to provide anatomical and functional information. 33,34 In cancer diagnosis, mapping of tissue pH can potentially be used to recognize malignant processes at an early stage since the accelerated glucose metabolism of cancer cells results in a decrease of the extracellular and increase of the intracellular pH (Warburg effect). 35,36 Several Gd(III)-based pH-sensitive SCA candidates were reported relying on the pH-dependent coordination of an ethylamine pendant arm.…”
mentioning
confidence: 99%
“…The most promising candidates are complexes of the essential Mn­(II) ion because it has acceptable relaxation enhancement properties and its homeostasis and transport in living systems guarantee very efficient elimination form the living systems, as it was observed for the [Mn­(PyC3A)] chelate recently. However, Mn­(II) complexes are in general labile, and only a few examples of inert Mn­(II) complexes are known. The release of Mn­(II) from its labile complexes may interfere with the MR signal generated as a result of SCA activation because the uncomplexed Mn­(II) ion or its adduct with human serum albumin (HSA) has considerably higher relaxivity ( r 1p = 7.92 and 54.6 mM –1 s –1 at 0.49 T and 25 °C) than the majority of the monohydrated low molecular weight Mn­(II) complexes ( r 1p values are typically in the range of 2.0–5.4 mM –1 s –1 ). ,, In addition, Mn­(II) has a PET isotope ( 52 Mn), which may offer a convenient way to follow the biodistribution of the agent during imaging as the local concentration of the complex can be determined by radioanalytical methods by using a cocktail of 52 Mn/ 55 Mn isotopic complexes . Furthermore, this isotopic mixture offers the possibility of combining PET ( 52 Mn) and MR ( 55 Mn) imaging modalities to provide anatomical and functional information. , …”
mentioning
confidence: 99%
“…A study demonstrated the relevance of the nursing team in the MRI room and during the exam, as these professionals use various skills such as knowledge of imaging techniques, information, preparation, communication and patient safety to guarantee that the exam goes well and to help improving the image by orienting and supporting the patient's immobility during the exam (5,19) .…”
Section: []Nursing Professionals' Work Include Positioning Patients I...mentioning
confidence: 99%
“…Different drugs can be used when applying these methods, such as contrast agents and radiopharmaceuticals. All this complex technological evolution justifies the nomenclature given by COFEn to this new nursing specialty (4,5) .…”
Section: Introductionmentioning
confidence: 99%
“…(5 ) A união de duas modalidades de imagem em um único equipamento, conhecidas como equipamento híbrido, como a tomografia por emissão abdominais superiores e pélvicos. (57) Em processos inflamatórios, estudo com PET/RM podem aumentar a sensibilidade com a sinergia dos dois equipamentos, possuindo uma definição anatômica e a informação funcional. Agentes biomodais como Fe 3 O com Cu ou F-FDG encapsulada por NP podem apresentar um aumento das propriedades relaxométricas mantendo as características radioativas e sem alterar suas funções químicas, podendo ser utilizadas como contraste para detecção de uma inflamação.…”
Section: Imagem Por Ressonância Magnética Como Alternativa Para Detecunclassified